ANALISIS KEBUTUHAN MAHASISWA PROGRAM STUDI PGSD UAD DALAM MATA KULIAH PEMBELAJARAN TERPADU DI SEKOLAH DASAR - Amaliyah Ulfah (Profesi Pendidikan Dasar, 2017)
Good mastery of integrated learning model is one of important competencies for primary school education students. Without good mastery, they will find it hard to design and do instruction in primary schools that involve a number of fields of study and themes. This study aims at investigating the needs of primary school education students in the course of integrated learning in Elementary school. This is a survey research which used questionnaire to collect the data. The population of this study were 318 primary school education students who took the course. It used proportionale stratified sampling with the number of samples as many as 178 students. The results indicate that the needs of students were related to course materials, including a variety of Elementary school students characteristics, types or models, procedures, and assessment in integrated learning. It is expected that the teaching methods of integrated learning course use direct practice in Elementary school. while the evaluation system is in written form and practice.